Prevalence of Mental Health and Substance Use Difficulties Among Sexual and Gender Diverse Youth During COVID-19: A Systematic Review and Meta-Analysis - Racine, Nicole; Deneault, Audrey-Ann; Eccles, Heidi; Hopley, Anara; Le, Milan; Labelle, Patrick R; Prada, Kevin; Colman, Ian (LGBT health, 2025)
Sexual and gender diverse (SGD) youth have been particularly vulnerable to mental health difficulties and substance use during the COVID-19 pandemic. However, estimates have varied across studies pointing to the potential for moderator variables. This meta-analytic and narrative synthesis provides estimates of the prevalence of mental health difficulties (anxiety, depression, suicidal ideation, suicide attempts) and substance use during COVID-19 among SGD youth. A comprehensive search strategy combining keywords and subject headings was designed and used across eight databases from inception to October 7, 2022. The search yielded 826 nonduplicate records of which 191 full-text articles were retrieved, evaluated, and extracted by two study authors. Data were analyzed from February 27 to March 1, 2023. Using random-effects meta-analyses, 19 studies from 18 independent samples with 10,500 participants were included. Pooled prevalence rates for clinically elevated anxiety, depression, and suicidal ideation were 55.4% [95% confidence interval (CI):45.9%-64.5%], 61.8% (95% CI: 50.9%-71.7%), and 50.9% (95% CI: 42.8%-59.0%). There was no evidence of publication bias. Suicide attempts and substance use were summarized narratively with rates of suicide attempts being greater than 20% across included studies and variable reporting of substance use across substance types. No moderators explained variability across studies. More than 50% of SGD youth experienced clinically elevated symptoms of anxiety, depression, and suicidal ideation during the COVID-19 pandemic, compared to prepandemic estimates for both SGD and non-SGD youth. Targeted resource allocation is needed to specifically address the needs of SGD youth.